The woman with the blue star - Jenoff, Pam (Park Row Books, 2021)
Inspired by the harrowing true stories of those who hid from the Nazis in the sewers, this emotional testament to the power of friendship follows Ella, an affluent Polish girl, as she helps Sadie and her pregnant mother survive despite the worsening dangers of the war.